Physical problem list accompanying the distress thermometer: Its associations with psychological symptoms and survival in patients with metastatic lung cancer. Issue 5 (11th March 2020) - McFarland, Daniel C.; Jutagir, Devika R.; Miller, Andrew; Nelson, Christian
Abstract: Background: The distress thermometer and problem list (DT&PL) is a recommended screening measure but the utility of the physical problem list (PPL) has not been evaluated in patients with metastatic lung cancer who typically have high rates of both physical and psychological symptoms. We hypothesized that the PPL will provide an accurate representation of lung cancer symptoms and be associated with concomitant distress, anxiety, depression, and worsened survival. Methods: Stage IV lung cancer patients (n = 116) reported physical symptoms from 22 PPL variables and completed the DT&PL for distress, general anxiety disorder‐7 for anxiety, and Patient Health Questionnaire 9 for depression. Inferential analyses were controlled for demographic and clinical characteristics. Results: The average number of physical problems was 4.7 (SD = 3.8) while the median was 3.0. Fatigue, sleep, pain, and breathing problems were most common. Physical symptom burden was associated with nonmarried/partnered status ( P = .003) and depression ( P  < .001) on multivariate analysis accounting for 43% of physical symptom burden variance. Greater number of physical symptoms and lower BMI were associated with worsened survival. Individual physical symptoms were most often associated with depression. Conclusion: The PPL of the DT&PL appears to have clinical utility given its associations with the most common lung cancer symptoms, depression, and worsened survival. In addition to its potential role in clinics worldwide already using the DT&PL, physical symptom burden on the DT&PL should trigger a concomitant psychological assessment.